Analysis of Motivation and Self-Confidence towards Teaching Effectiveness with Teacher Professionalism as an Intervening Variable at SMA Maha Putra Tello Makassar - Rahmat Hidayat Samsuddin; Dian A.S. Parawansa; Haeriah Hakim (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The scientific investigation aims to analyze the direct influence of motivation and self-confidence on teacher professionalism and teaching effectiveness, examine the direct impact of teacher professionalism on teaching effectiveness, and explore the indirect effect of motivation and self-confidence on teaching effectiveness through teacher professionalism at SMA Maha Putra Tello Makassar. The research employs a quantitative approach with an explanatory research design, using a sample of 343 respondents comprising all students at SMA Maha Putra Tello Makassar. Data collection techniques involve observation and questionnaire distribution. The data analysis employs advanced quantitative methods, with SEM-PLS as the analytical tool. The study's findings reveal that self-confidence has a significant and positive influence on teacher competence, while motivation also exhibits a significant and positive effect on teacher competence. Furthermore, professionalism has a positive and significant impact on teaching effectiveness. Moreover, it is observed that self-confidence, mediated by professionalism, positively and significantly affects teaching effectiveness, as does motivation through professionalism. These results imply that teaching effectiveness, as an indicator of teacher success, is determined by the combination of teacher self-confidence and motivation, mediated by their professionalism in delivering effective learning to students.